Research for development: The importance of a learning resource (Library) for building up a modenn University (Library Cooperation Cluster, 2025)
The conference focused on the critical role of learning resources, particularly university libraries, in the development of a modern university. It was jointly organised by Mzumbe University and Adger University College, Kristiansand, and held at Whitesands Hotel, Dar es Salaam, Tanzania. The event brought together participants and experts from Tanzania and Norway to discuss key themes related to library and information services in higher education. The main outcomes of the conference highlighted the importance of resource sharing and institutional collaboration; the evolving role of university libraries in the era of information explosion and technological advancement; the development of electronic resource-sharing networks; and the management of university libraries in the digital age. Other discussions centred on the implementation of information literacy programmes, the relationship between internet access and poverty reduction, IT adoption in Tanzanian educational institutions, and the role of information technology in national development.